Optimization of the Role of Uryanmin Satintelkam Polres Sragen in Publication Services of Police Record Certificates to Provide Excellent Public Services - Sihombing, Daniel Marsauli (Advances in Police Science Research Journal, 2024)
The Community Satisfaction Index is a measure of the success of a public service. The Indonesian National Police must provide excellent public services. One form of public service provided is a statement letter, one of which is a Certificate of Police Records The decline of Community Satisfaction Index in Certificate of Police Records issuance services at the Sragen Police is the background of this research. The form of the research approach used by the author is a qualitative approach, the object of his research is regarding the role of Administrative Service Affairs for the Sragen Police Satintelkam in issuing SKCK and knowing the factors that cause a decrease in the community satisfaction index for SKCK issuance services by uryanmin satintelkam Sragen Police. From the research results, uryanmin’s role in providing excellent public services is quite good, but there are still several things that need to be optimized so that uryanmin’s role becomes even better.